2014
DOI: 10.2147/opth.s69501
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between amblyopic and fellow eyes in unilateral amblyopia using spectral-domain optical coherence tomography

Abstract: PurposeTo compare the macular retinal thickness and characteristics of optic nerve head (ONH) parameters in amblyopic and fellow eyes in patients with unilateral amblyopia.Patients and methodsA total of 21 patients with unilateral amblyopia (14 patients with anisometropic amblyopia, four patients with strabismic amblyopia, and three patients with both) were examined using spectral-domain optical coherence tomography. The mean age of the patients was 8.5±3.5 years. The examined parameters included the mean macu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
0
19
4
Order By: Relevance
“…Our study also compared optic disc structures (disc area, cup area, and horizontal-vertical cup/disc ratios) but failed to find a significant difference between amblyopic and fellow eyes. These results counter the data of Araki et al [ 30 ], who found a significantly larger rim area and smaller cup/disc ratios (average, vertical, and horizontal) in amblyopic eyes. This might have been because their study population included strabismic, anisometropic, and mixed-type amblyopic eyes.…”
Section: Discussioncontrasting
confidence: 95%
“…Our study also compared optic disc structures (disc area, cup area, and horizontal-vertical cup/disc ratios) but failed to find a significant difference between amblyopic and fellow eyes. These results counter the data of Araki et al [ 30 ], who found a significantly larger rim area and smaller cup/disc ratios (average, vertical, and horizontal) in amblyopic eyes. This might have been because their study population included strabismic, anisometropic, and mixed-type amblyopic eyes.…”
Section: Discussioncontrasting
confidence: 95%
“…We thought that the adjustment of AL by SE might lead to statistically accurate results. This was in disagreement with Araki et al; 52 they reported a significant correlation between the AL and CMT changes, which might be owing to the relatively small sample size (21 subjects with less difference in the mean SE among the study subjects). By contrast, Kok et al 53 concluded consistent results with our findings; they did not find an abnormal relation between the AL and CMT in amblyopic eyes.…”
Section: Discussioncontrasting
confidence: 74%
“…Previous studies that used SD-OCT to evaluate the inner retinal thickness reported finding no significant differences in the GCL+IPL or GCC thicknesses between the amblyopic eyes and the fellow and normal control eyes [ 16 , 27 29 ]. In contrast, Park et al [ 30 ] reported that the GCL+IPL thickness was thinner in amblyopic eyes versus the fellow eyes.…”
Section: Discussionmentioning
confidence: 99%